2020
DOI: 10.1088/1755-1315/575/1/012212
|View full text |Cite
|
Sign up to set email alerts
|

Shaping and maintaining anti-littering behavior of the community in Indonesia

Abstract: Littering behavior of the community is blamed as one of the causes of waste problems in Indonesia. Many efforts have been conducted, but unfortunately, the effects were sometimes not optimal or only successful temporarily. The current study was conducted using the literature review method to find a solution to this problem. The results indicate that to form anti-littering habits, it is necessary to increase knowledge, and correct perceptions about waste, establish communication, and collaboration of all stakeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Some have carried out campaigns or counseling and assistance to implement 3R, set up waste banks, compost, decompose organic waste using magot, make regulations on waste, supervise and enforce laws, and provide adequate facilities and infrastructure, efficient transport routes using GPS. There are even areas that have converted waste into energy (Alqahtani et al, 2022;Bulekova et al, 2022;Fauzan et al, 2022;Janetasari & Bokányi, 2022;Ramaditya et al, 526 2022;Pratama et al, 2022;Sulistyaningsih, 2022;Sunaryani, 2022;Wahyuni et al, 2022;Xu et al, 2017). However, until now, waste management has not been satisfactory; for example, the 3R activities, namely reuse, reduce, and recycling, have not run optimally (Brotosusilo et al, 2022;Grishaeva et al, 2022;Mwanza et al, 2018;Ramaditya et al, 2021;Oktariani et al, 2022;Sulistyaningsih, 2022;Wahyuni et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some have carried out campaigns or counseling and assistance to implement 3R, set up waste banks, compost, decompose organic waste using magot, make regulations on waste, supervise and enforce laws, and provide adequate facilities and infrastructure, efficient transport routes using GPS. There are even areas that have converted waste into energy (Alqahtani et al, 2022;Bulekova et al, 2022;Fauzan et al, 2022;Janetasari & Bokányi, 2022;Ramaditya et al, 526 2022;Pratama et al, 2022;Sulistyaningsih, 2022;Sunaryani, 2022;Wahyuni et al, 2022;Xu et al, 2017). However, until now, waste management has not been satisfactory; for example, the 3R activities, namely reuse, reduce, and recycling, have not run optimally (Brotosusilo et al, 2022;Grishaeva et al, 2022;Mwanza et al, 2018;Ramaditya et al, 2021;Oktariani et al, 2022;Sulistyaningsih, 2022;Wahyuni et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, until now, waste management has not been satisfactory; for example, the 3R activities, namely reuse, reduce, and recycling, have not run optimally (Brotosusilo et al, 2022;Grishaeva et al, 2022;Mwanza et al, 2018;Ramaditya et al, 2021;Oktariani et al, 2022;Sulistyaningsih, 2022;Wahyuni et al, 2022). The obstacles are the low level of citizen participation, weak supervision, low collaboration with various stakeholders, and limited facilities, infrastructure, and budget (Fauzan et al, 2022). This research is intended to show the level of community participation in waste management that will support the agricultural sector.…”
Section: Introductionmentioning
confidence: 99%
“…Littering is a behavioral problem that requires urgent solutions [12]. Studies have shown that the way to deal with the littering problem is to combine means by improving infrastructure, legislation and enforcement, advocacy, and education in the field [21,22]. As an illustration, it was determined that enforcement exhibited greater efficacy in clean environments compared to polluted ones [23].…”
Section: Introductionmentioning
confidence: 99%
“…Excessive use of environmentally unfriendly products will also impact the surrounding environment (Li & Wang, 2019). The behavior of the Indonesian people who have a habit of littering causes many environmental impacts (Dhahir, 2020). The impact of dumping waste in the river is that it will become a nest of disease for residents who live around the banks of the Bengawan Solo River (Baptiste, Gravitiani, & Eric, 2021).…”
Section: Introductionmentioning
confidence: 99%